Consumers' purchase intention towards genetically modified soybean products in Malaysia - Wong, Kelly Kai Seng; Son, Welson Chin Vui; Phuah, Kit Teng; Sharifuddin, Juwaidah; Ali, Fazlin (International Society for Southeast Asian Agricultural Sciences, 2018)
In Malaysia, soybean products are a convenient and a popular daily food product, however, the main raw material used to produce these soybean products has been partly changed from the traditional soybean to the imported GM soybean. While the GM soybean products are commercially sold in the market, not all the consumers take notice or are aware of it. There is lack of information sharing between GM soybean products' producers and consumers and the argument about the safety of GM product is still a big issue among consumers. As the GMOs are relatively new to Malaysian consumers, the National Biotechnology Directorate is stepping up its efforts to implement public awareness programs on biotechnology. Thus, this study will attempt to conduct the consumer research to provide insights on how likely consumers are willing to purchase genetically modified soybean. The purpose of this study is to determine the factors affecting consumers' intention to purchase genetically modified soybean products in Malaysia. Multistage and convenient sampling was used in selecting 215 respondents who were surveyed using self-administered questionnaires. Descriptive analysis, reliability test, exploratory factor analysis and binary logistic regression analysis were used to accomplish the objective of this study. The binary logistic result shows that product attribute, consumer attitude, and gender influenced consumers' intention to purchase genetically modified soybean in Malaysia. Understanding the consumer's intention will help the food producer and manufacturer to identify the consumer preferences for GM food products and will help prevent losses in market share of soybean products.